THE EFFECTIVENESS OF AGREEMENT HUDAYBIYA - Mahlil Ismail (Jurnal Ilmiah Peuradeun, 2015)
This study aims to answer the problem of Hudaybiya conflict occurred in six moved when Prophet Muhammad and Moslems umrah to Mecca. The conflict arises because of concerns the Quraysh against the Moslems will take revenge on the expulsion of the Prophet to migrate to Madina. The conflict resolution begins Budeil Quraysh sent to the Prophet in Hudaybiya to develop measures of peace. The method used prophet is interactive dialogue. The method is very effective in resolving the conflict once the right solution and the right. Diplomacy built Prophet as an effective approach to demonstrate in peace Hudaybiya. Mutual agreement between the Prophets with Suheil is the two sides agreed to a ceasefire for 10 years. Diplomacy built Prophet proven success Hudaybiya agreement. Effectiveness Hudaybiya agreement described increased number of Moslems, Islam weakened the strength of the enemy, and terrain propaganda expanded, and maintained the dignity of women. The success of the negotiations and diplomacy cannot be separated from the attitude wise, polite, patient, gentle, and the genius of the character's personality majesty that provide energy and great intelligence in his preaching activity.